Variation in the use of Fontan fenestration in the current surgical era. (March 2019) - Hill, Garick D.; Ghanayem, Nancy S.; Hraska, Viktor; Jacobsen, Roni M.; Mitchell, Michael E.; Woods, Ronald K.; Ginde, Salil
Abstract: Fontan fenestration reduces chest tube duration and shortens post-operative length of stay but is not universally performed. Using a large national database, we sought to describe current use of the Fontan fenestration, including factors associated with placement. The Virtual Pediatric System database was queried to identify patients with the Society of Thoracic Surgery code for a Fontan procedure during their admission from January 2009 until June 2016. Those undergoing a fenestrated Fontan were compared to those undergoing a non-fenestrated Fontan. Of the 1695 patients, 1084 (64%) had a fenestration placed. There was variation between centers with the range of fenestration placement being 8 to 100%. Those with a fenestration placed had lower weight, despite similar age, and were more likely to have a single right ventricle. Those with a fenestration had lower systolic blood pressure and greater need for mechanical ventilation within the first hour of admission to the intensive care unit after Fontan. Most patients still have a fenestration placed at the time of Fontan but this varies markedly by center. Fenestration placement is more common in higher risk patients including those with a systemic right ventricle. Further study is necessary to determine specific patient populations that benefit from fenestration placement at the time of Fontan. Highlights: The majority of patients have a fenestration placed at the time of Fontan. There is marked variation between centers in the use of Fontan fenestration. Those patients receiving fenestration are higher risk patients.